The Demographic Components of the Syrian Region in Ancient Times - Amor, BOUSBIA (Journal of Ecohumanism, 2025)
This study examines the human migrations of Semitic peoples who set out from the southern Arabian Peninsula toward the Syrian region. These groups spread both westward and eastward across historical Syria, forming branches known as the Amorites, Arameans, and Canaanites. Among the Canaanites, another branch can be distinguished: those who settled along the Syrian coast, known as the Phoenicians. All of these human groups succeeded in forming political entities during their presence in the Syrian region, whose strength and weakness varied over time, until the area was subjected to invasions by major empires such as the Akkadian, Babylonian, Assyrian, Chaldean, and Persian empires. Despite this, some of these Semitic political entities managed to survive until the Roman era.